Petrie polygons, Fibonacci sequences and Farey maps - Singerman, David (Ars mathematica contemporanea, 2016)
We consider the regular triangular maps corresponding to the principal congruence subgroups ?$Γ(n)$? of the classical modular group. We relate the sizes of the Petrie polygons on these maps to the periods of reduced Fibonacci sequences.
Keywords: Fibonacci sequence; Fibonaccijevo zaporedje; Petrie polygon; Petriejev poligon; regular map; regularni zemljevid